SPE European Formation Damage Conference 1997
DOI: 10.2118/38183-ms
|View full text |Cite
|
Sign up to set email alerts
|

Andrew/Cyrus Horizontal Well Completions

Abstract: The Andrew Field produces from a Palaeocene sandstone saturated oil reservoir, in UK North Sea Blocks 16/27a and 16/28. Cyrus is a small subsea tieback, 7km NE of Andrew, containing undersaturated oil. Both fields are operated by BP Exploration. Field development was sanctioned in 1994, some 20 years after discovery. During those 20 years, numerous development concepts failed to achieve the expected economic return. However, in 1992 the Andrew well count was reduced from 18 to 10 by changing from vertical to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…This is substantially larger than the Geertsma approximation, and thus oriented perforating in a well without sand control provides a distinct advantage over using phased perfs, at least theoretically. Advantages of oriented perforating have been reported from the field by several authors 10,11,12,13,14 . …”
Section: Stress Logsmentioning
confidence: 99%
“…This is substantially larger than the Geertsma approximation, and thus oriented perforating in a well without sand control provides a distinct advantage over using phased perfs, at least theoretically. Advantages of oriented perforating have been reported from the field by several authors 10,11,12,13,14 . …”
Section: Stress Logsmentioning
confidence: 99%
“…The technique of optimal phased oriented perforating was applied to the Eocene C reservoir in Lake Maracaibo, Venezuela 10 . Another case is the Andrew field in the North Sea where the perforations were oriented at an angle +/-25 degrees in the topside in horizontal wells 11 . In both cases the perforating strategy used deep penetrating charges.…”
Section: Oriented Perforatingmentioning
confidence: 99%
“…Single-shot perforation and flow experiments can be used to confirm the underbalance value chosen. Selective Perforating: In formations where the strength varies drastically with depth, by avoiding perforating in sections that are weaker, one can maintain sand-free production throughout the reservoir life 11 . Both productivity analysis using nodal analysis programs (to study the impact of partial penetration on productivity) and strength analysis (using methods mentioned in previous section) need to be carried out prior to making this choice.…”
Section: Other Considerationsmentioning
confidence: 99%
“…1 Essentially using horizontal wells with cemented liners was the strategy chosen to allow easy access and water shutoff later in the field life. Studies showed that the formation was sensitive to kill fluids, so a "no-kill" perforating solution was chosen using a downhole isolation valve with lengths in excess of 1000 m perforated on each well.…”
Section: Introductionmentioning
confidence: 99%